Ascorbate-Glutathione Cycle Genes Families in Euphorbiaceae: Characterization and Evolutionary Analysis - Douglas Jardim-Messeder; Ygor de Souza-Vieira; Lucas Corrêa Lavaquial; Daniela Cassol; Vanessa Galhego; Gabriel Afonso Bastos; Thais Felix-Cordeiro; Régis Lopes Corrêa; Marcel Zámocký; Márcia Margis-Pinheiro; Gilberto Sachetto-Martins (Biology, 2022)
Ascorbate peroxidase (APX), Monodehydroascorbate Reductase (MDAR), Dehydroascorbate Reductase (DHAR) and Glutathione Reductase (GR) enzymes participate in the ascorbate-glutathione cycle, which exerts a central role in the antioxidant metabolism in plants. Despite the importance of this antioxidant system in different signal transduction networks related to development and response to environmental stresses, the pathway has not yet been comprehensively characterized in many crop plants. Among different eudicotyledons, the Euphorbiaceae family is particularly diverse with some species highly tolerant to drought. Here the APX, MDAR, DHAR, and GR genes in Ricinus communis, Jatropha curcas, Manihot esculenta, and Hevea brasiliensis were identified and characterized. The comprehensive phylogenetic and genomic analyses allowed the classification of the genes into different classes, equivalent to cytosolic, peroxisomal, chloroplastic, and mitochondrial enzymes, and revealed the duplication events that contribute to the expansion of these families within plant genomes. Due to the high drought stress tolerance of Ricinus communis, the expression patterns of ascorbate-glutathione cycle genes in response to drought were also analyzed in leaves and roots, indicating a differential expression during the stress. Altogether, these data contributed to the characterization of the expression pattern and evolutionary analysis of these genes, filling the gap in the proposed functions of core components of the antioxidant mechanism during stress response in an economically relevant group of plants.